Предмет: Математика,
автор: sssssssssss3
переобразуйте выражение tga*ctga-sin2a
Ответы
Автор ответа:
0
tga*ctga-sin2a=1-sin2a=2cosa
Автор ответа:
0
-1;0;sin2a;cos2a;1
Автор ответа:
0
tga*ctga-sin2a=(sina/cosa)*(cosa/sina)-2sina*cosa=1-2sina*cosa=sin^+cos^2-2sina*cosa=(sina-cosa)^2
Автор ответа:
0
Извините пропустила sin^2
Похожие вопросы
Предмет: Українська мова,
автор: alinapechena9
Предмет: Қазақ тiлi,
автор: nursatrymkul294
Предмет: Математика,
автор: bogdanshapoval0804
Предмет: Литература,
автор: СаШуЛя64раш
Предмет: Химия,
автор: Ergesheva1